Patterns of Eye Movements When Observers Judge Female Facial Attractiveness - Zhang, Yan; Wang, Xiaoying; Wang, Juan; Zhang, Lili; Xiang, Yu (Frontiers in Psychology, 2017)
The purpose of the present study is to explore the fixation patterns for the explicit judgments of attractiveness judgments and infer which features are used for attractiveness. Facial attractiveness is of high importance for human interaction and social behavior. Behavioral studies on the perceptual cues for female facial attractiveness suggested three potentially important features: averageness, symmetry, and sexual dimorphy. However, none of these studies explained which regions of stimulus images influence observers’ judgments. Therefore, the present research recorded the eye movements of 24 male observers and 19 female observers as they rated a set of 30 photographs of female facial attractiveness. Results demonstrated the following: (1) Fixation is longer and more frequent on the noses of female faces than on their eyes and mouths (no difference exists between the eyes and the mouth); (2) The average pupil diameter at the nose region is bigger than that at the eyes and mouth (no difference exists between the eyes and the mouth); (3) the number of fixations of male participants was significantly more than female participants. (4) Observers first fixate on the eyes and mouth (no difference exists between the eyes and the mouth) before fixating on the nose area. In general, participants attend predominantly to the nose to form attractiveness judgments. The results of this study add a new dimension to the existing literature on judgment of facial attractiveness. The major contribution of the present study is the finding that the area of the nose is vital in the judgment of facial attractiveness. This finding establish a contribution of partial processing on female facial attractiveness judgments during eye-tracking.